2011
DOI: 10.5028/jatm.2011.03022411
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of wind profile in the surface layer at the Alcântara Launching Center

Abstract: Análise estatística do perfi l de vento na camada limite superfi cial no centro de lançamento de AlcântaraResumo: A análise estatística do perfi l de vento obtido junto à torre anemométrica do Centro de Lançamento de Alcântara foi realizada com base nos dados de vento (direção e velocidade), coletados no período de 1995 a 1999, obtidos em seis níveis diferentes: 6,0; 10,0; 16,3; 28,5; 43,0 e 70,0 m. Nesta análise, foram considerados os meses característicos das estações chuvosa (março) e seca (setembro), na r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…The wind is predominantly from the sector north-north-east (NNE), with ~ 70% of the time with winds coming from NE. This result is somewhat similar to what Gisler et al (2011) found using a longer wind data set. They showed that for dry season, for a period between the years 1996-1999, the predominant winds were 45% from NE and 40% from ENE, and the remaining 15% from NNE and E. In a scale of about 10 km, the costal line is aligned north-north-west (NNW) -south-south-east (SSE), and winds reaching the tower and Sonic A are necessarily from the ocean (Fig.…”
Section: Internal Boundary Layerssupporting
confidence: 90%
See 3 more Smart Citations
“…The wind is predominantly from the sector north-north-east (NNE), with ~ 70% of the time with winds coming from NE. This result is somewhat similar to what Gisler et al (2011) found using a longer wind data set. They showed that for dry season, for a period between the years 1996-1999, the predominant winds were 45% from NE and 40% from ENE, and the remaining 15% from NNE and E. In a scale of about 10 km, the costal line is aligned north-north-west (NNW) -south-south-east (SSE), and winds reaching the tower and Sonic A are necessarily from the ocean (Fig.…”
Section: Internal Boundary Layerssupporting
confidence: 90%
“…2) with a wind profile composed by six propeller anemometers at the levels 6, 10, 16, 28, 43, and 70 m. A 3D sonic anemometer (Sonic B), from Campbell Scientific, Inc. (model CSAT3), was mounted on the tower at 9.5 m above ground level (AGL). Gisler et al (2011) describes some climatological features of this tower. At 700 m inland, there was a second sonic anemometer (Sonic A -shorter segment in Fig.…”
Section: Elevation Range (M)mentioning
confidence: 99%
See 2 more Smart Citations
“…Por exemplo, Pimentel et al (2014) apresentam um estudo para a região metropolitana do Rio de Janeiro, analisando efeitos da topografia como também a relação com as brisas marítima e terrestre como ferramenta de auxílio na gestão ambiental do município. Outra aplicação importante é a caracterização do escoamento nas vizinhanças de aeroportos e bases de veículos lançadores de satélite como estudo diagnóstico (SILVA et al, 2009;GISLER;FISCH;CORREA, 2011). Análises da estabilidade atmosférica nos arredores de usinas nucleares (OLIVEIRA JR.; PIMENTEL; LANDAU, 2010) e estudos de morfodinâmica dunar para identificar vestígios arqueológicos (SILVEIRA; SERPA, 2015) são outros exemplos de aplicação de metodologia similar à utilizada neste estudo.…”
Section: Métodosunclassified